First characterisation and conservation needs of a large maternity colony of lesser horseshoe bats (Rhinolophus hipposideros) in Aljezur, Portugal - G. Calderoni; S. Krzemińska; M. Górska; M. Paladini; M. Ren; G. Apoznański; A. Bamberger; A. Blum; T. Kokurewicz (The European Zoological Journal, 2024)
A new maternity colony of lesser horseshoe bats (Rhinolophus hipposideros) was found and described in an abandoned building in Aljezur, Portugal. Between June 25 and July 4, 2022, we conducted emergence and juvenile counts, took light intensity measurements during emergence times and evaluated microclimatic conditions inside the roost, namely temperature and relative humidity. Moreover, we took ultrasound recordings in the open and performed transects to locate foraging areas and commuting corridors. We found the colony amounted to at least 501 individuals (371 adults and 130 juveniles), currently the largest known in Portugal and one of the biggest in Europe. Sixteen matching echolocation calls were recorded away from the colony near a water reservoir, a probable foraging area together with the Vale da Telha valley connecting the roost to the water body, which may also serve as a commuting corridor. Considering the threatened conservation status of the lesser horseshoe bat, the large colony size and its lack of protection, we proposed several conservation measures aimed at preserving the colony. We hope our recommendations will be included in the management plan currently being prepared for the Natura 2000 site Costa Sudoeste. Following up on this research, a radio-tracking study would definitively confirm the bats’ movements and foraging grounds.